REFLECTION OF FOLK TRADITIONS IN THE BALLAD OF ROBIN HOOD (Web of Discoveries: Journal of Analysis and Inventions, 2024)
This article focuses on the time of Robin Hood and the customs that existed during that time. In order to make the topic more clear, let's show the traditions highlighted in the work throughout the article. In addition, information is given on the concept of ballad and when this term entered the language.